2009
DOI: 10.4103/0970-9371.55224
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytologic grading in prognostication of invasive breast carcinoma

Abstract: Background:Evaluation of cytologic features is indispensable in the preoperative diagnosis and grading of infiltrating ductal breast carcinoma (CA) in fine-needle aspiration cytology (FNAC) material and this method can also provide additional information regarding intrinsic features of the tumor as well as its prognosis.Aim:This study has been done to evaluate comparatively the cytologic and histomorphologic grading of infiltrating ductal carcinoma of breast with specific reference to lymph node metastasis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 16 publications
(20 reference statements)
7
35
0
Order By: Relevance
“…[26][27][28] On correlating the cytological grading by RCG method with histopathology the concordance rate ranged from 56.9% to 89.1% by various studies. [9,27,[29][30][31][32][33][34][35][36][37] Phukan JP et al and Nggada HA et al, had found the overall sensitivity and specificity of 72.2% & 97.5% and specificity of 100% & 98.7% in cytological grading of breast carcinoma respectivily. [33,3] In present study, which includes both benign and malignant breast lesions has a overall sensitivity of 86% and specificity of 50%.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] On correlating the cytological grading by RCG method with histopathology the concordance rate ranged from 56.9% to 89.1% by various studies. [9,27,[29][30][31][32][33][34][35][36][37] Phukan JP et al and Nggada HA et al, had found the overall sensitivity and specificity of 72.2% & 97.5% and specificity of 100% & 98.7% in cytological grading of breast carcinoma respectivily. [33,3] In present study, which includes both benign and malignant breast lesions has a overall sensitivity of 86% and specificity of 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al 10 showed a concordance value of 84%. A study by Milentijevic et al 11 also show a concordance value of 81%.…”
Section: Correlation Of Lymph Node Status With Tumour Sizementioning
confidence: 99%
“…These studies coincide with the present study. Khan et al 10 states that higher concordance was found among Grade 1 tumours (92.3%). Several studies states that concordance was high among high-grade tumours.…”
Section: Correlation Of Lymph Node Status With Tumour Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The breast carcinomas were graded cytologically by Robinson's Cytological Grading system (Table 1).Histological grading of H&E stained tissue sections was done by Modified Scarff Bloom Richardson method (Table 2). Scores: Grade I (well differentiated) 3-5; Grade II (moderately differentiated) 6-7; Grade III (poorly differentiated) [8][9] Concordance was calculated between cytological and histological grading systems for all the grades. Kappa statistical analysis was done to see the strength of agreement between the two grading systems.…”
Section: Methodsmentioning
confidence: 99%